"Usual" cannabis abuse producing unusual consequences - Sieber, Cornel; et al. (Deutsche Medizinische Wochenschrift, 2007)
Case history: A 17-year-old male presented in an agitated,.deranged state with rapidly increasing swelling of the neck. Except for regular abuse of cannabis there was no medical history of note. He had a sinus tachycardia (130 bpm), a slow pupillary reflex, bilateral hyposphagma and subcutaneous emphysema around the neck and shoulders.Investigations and diagnosis: Laboratory tests showed elevated inflammatory markers. The chest X-ray demonstrated a bilateral pneumothorax and large subcutaneous emphysema. Subsequent computed tomography of neck and thorax showed an extensive pneumomediastinum and the described subcutaneous emphysema. There was no evidence of a ruptured trachea or esophageal perforation. The underlying cause was presumed to have been a Valsalva maneuver during marijuana smoking.Treatment and course: As the pneumothorax was completely reabsorbed, no chest drains were inserted and the patient was transferred to our toxicological intensive care unit. Recurring drug-induced psychosis had to be treated with repeated doses of haloperidol. The emphysema was slowly reabsorbed without any further complication. The patient was transferred back to a psychiatric ward after five days.Conclusion: Although cannabis is thought to be one of the "safe" drugs, its abuse can have life-threatening effects. One complication is the occurrence of a pneumothorax after a Valsalva maneuver. As the rate of cannabis abuse has been increasing during the last few years, the risk of life-threatening complications should be mentioned in relevant publications and as part of drug education Patients presenting with dyspnea should always be carefully questioned about possible drug abuse.
Keywords: cannabis; marijuana; pneumothorax; pneumomediastinum; Valsalva maneuvers; drug induced psychosis